Doing phonetic transcription on Moodle - Aperliński, Grzegorz; Łodzikowski, Kacper; Weckwerth, Jarosław (My University, 2013)
Moodle is an open-source learning management system, one of the leading e-learning platforms in use today at all levels of education. It has been successfully used in the teaching of phonetics and pronunciation (e.g. Ashby et al. 2009; Wilson 2008). This paper will present various aspects of the use of phonetic transcription on Moodle on the example of a b-learning module supporting a course in English Phonetics and Phonology within a university programme in English Studies. First, we will present our approach to interactive transcription exercises based on two Moodle question types: multiple choice and short answer with input from a custom-developed keyboard with IPA symbols. Pre-programmed hints for both wrong and correct answers provide comprehensive just-in-time feedback, which creates a more personalised and effective learning environment. A survey on students’ attitudes to Moodle solutions shows, however, that students prefer paper exercises because they can be completed faster. Various ways of delivering phonetic transcription to participants for presentation purposes will be presented (image vs. PDF vs. Flash vs. Unicode text), and their relative strengths and weaknesses will be discussed. Methods of styling the Unicode text of phonetic transcription as part of Moodle web pages will be described. Finally, we will demonstrate how the preparation of quiz questions can be automated and performed in batch mode offline (bypassing the often cumbersome question-building interface of Moodle) using widely available word-processing software such as MS Word. (The poster contains links to templates and tutorials. Feel free to contact the authors in case of any questions.)
Poster presented at the 3rd International Conference on English Pronunciation: Issues & Practices
Keywords: Computer-assisted language learning; e-learning; Moodle; phonetic transcription; phonetics teaching and learning; EFL pronunciation teaching and learning